Cell death and antioxidant responses in Mytilus galloprovincialis under heat stress: Evidence of genetic loci potentially associated with thermal resilience - Dimitrios K. Papadopoulos; Basile Michaelidis; Ioannis A. Giantsis (PLoS ONE, 2025)
The global seawater temperature is expected to further rise in the following years. While species have historically adapted to climatic variations, the current pace of climate change may exceed their ability to adapt. The abnormally increased seawater temperatures occasionally lead to high mortalities of marine bivalve mollusks, threatening the productivity of aquaculture and the sustainability of wild populations. This study investigates the antioxidant and cell death mechanisms of the Mediterranean mussel Mytilus galloprovincialis during a 25-day exposure to temperatures of 24°C, 26°C, and 28°C, by analyzing the transcription of key genes and assessing the oxidative damage on days 1, 3, 12, and 25. In addition, individuals resilient (survived at 28°C until day 30) and susceptible (died early at 26°C and 28°C) to thermal stress were collected to investigate potential polymorphisms in associated genes. The results showed increased transcription of antioxidant genes at higher temperatures. Elevated pro-apoptotic indices were initially observed at 26°C and a higher mortality than at 28°C. However, final mortality was much higher at 28°C. At 26°C, mussels exhibited the highest oxidative damage and pro-apoptotic indices after 25 days. At 28°C, although oxidative damage occurred after 24 hours, survivors maintained a prolonged activated antioxidant defense and increased lc3b transcription, which likely contributed to the observed reduction of pro-apoptotic and oxidative damage metrics on day 25, compared to 26°C. Further, the coding sequences of catalase, intracellular Cu-Zn superoxide dismutase (Cu-Zn sod), and fas-associated protein with death domain (fadd) from heat-resilient and heat-susceptible mussels were analyzed. Based on statistical correlation of nucleotide and genotype frequencies with resilience phenotypes, two novel single nucleotide polymorphisms (SNPs) in Cu-Zn sod and one in fadd were detected, potentially correlating with thermal stress resilience. These findings offer valuable insights into the physiological and genetic adaptations of M. galloprovincialis to rising temperatures and highlight loci potentially linking to thermal resilience.